Study of planting density and canopy cover in open spaces in Budapest: Case Studies Part 1 – Móricz Zsigmond Square - Tóth, Barnabás; Doma-Tarcsányi, Judit; Szabó, Krisztina (4D Journal of Landscape Architecture and Garden Art, 2023)
Trees in public open spaces are an important part of the urban green space system, which has to adapt to increasingly difficult conditions due to urbanisation, climate change and human activity. Green spaces are a major factor in improving the microclimate, helping to protect biodiversity and playing an important aesthetic role, so they need to be preserved and enhanced. In our country, since the 2000s, a large number of studies and civil initiatives have highlighted the importance of green spaces, but typically from a quantitative approach. However, improving the quality of planting is an equally important task. Our research assesses the canopy cover of trees in open spaces in Budapest in terms of planting density, with a focus on the planting distance of trees in certain squares and streets and the resulting cover values. In our studies, we have considered the quantitative and qualitative variation in crown canopy cover at the time of planting and in maturity, so we can formulate ideal planting suggestions based on the environment, requirements and characteristics (crown shape, growth vigour) of each taxa. In the series of case studies, we first studied the woody species of one of the most important intermodal nodes of Budapest, Móricz Zsigmond Square and Bartók Béla Street. The canopy cover of the square reaches the ideally defined minimum canopy cover of 25-30% in 5-7 years. Considering canopy cover and planting density, it was found that in 2023 the canopy cover of the trees in the Móricz Zsigmond square averages 13%, while at maturity it will cover more than 50%. This means that about half of the tree crowns will be able to have the highest potential impact in terms of ecosystem services.